A bioactivity guided study on the anti-gonococcal and anti-inflammatory activity of Ficus abutilifolia stem bark extracts - Tshikalange, T.E. (Thilivhali Emmanuel) (University of Pretoria, 2022)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2022.